PERSPECTIVE THE USE OF ARTIFICIAL INTELLIGENCE (AI) TO COMPLETING MATHEMATICAL ASSIGNMENTS: EXPLORING STUDENTS' EXPERIENCES - Baharuddin (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
Artificial intelligence has an impact on all walks of life with its use still requiring more in-depth study in completing assignments, especially mathematics, so the aim of the research is to explore further the use of artificial intelligence in helping complete student assignments, with the type of research chosen being qualitative descriptive research. . The research subjects used came from 41 students of the Actuarial Science study program, Makassar State University, semester I 2024/2025. In data collection, an instrument was used in the form of a picture sheet on the use of artificial intelligence. The questionnaire is prepared in the form of an open questionnaire which is answered by students. The analysis process for research data was carried out in a qualitative descriptive manner. In accordance with the results of the analysis, it was concluded that the use of artificial intelligence has been widely used by actuarial science study program students, especially in working on mathematics problems. Commonly used types of artificial intelligence include ChatGPT, Cici AI, Gemini AI, Mathlab, Photomath, Question AI, and Google Lens. Its use has a good impact, but it must also be supported by a deeper understanding of the tasks to be completed.